Development of PBL-Based Learning Tools Integrating Local Wisdom Through Lesson Study at SMAS Plus Muhammadiyah Merauke - Ekasari, Aprilita; Algiranto, Algiranto; Rezki, Andi (Medan Resource Center, 2025)
This community service aims to implement the Problem-Based Learning (PBL) model through blended learning by integrating Papua’s local wisdom, as a result of collaborative efforts between lecturers and teachers, to enhance students’ Higher Order Thinking Skills (HOTS). The specific objectives include: (1) developing sustainable partnerships between lecturers, school teachers, and industry practitioners as end-users of graduates; (2) improving lecturers’ pedagogical competence in shaping Pancasila student profiles; (3) fostering a professional learning community through the application of lesson study principles; (4) discovering innovative and contextual learning models aligned with higher education demands; and (5) increasing research output and publications involving lecturers, schools, and industry. The method used was a collaborative action approach involving PBL socialization, lesson planning, implementation, and reflection conducted over two months. Activities were carried out through blended learning formats and were focused on contextual content based on local Papuan potential. The program involved 6 lecturers and 8 high school teachers, and was attended by 60 students. Results show a significant improvement in students’ HOTS as observed in project outcomes and reflection sessions. Additionally, participating lecturers reported improved pedagogical collaboration and cross-sector engagement. In conclusion, the program effectively strengthened lecturer–practitioner collaboration, enhanced HOTS through localized PBL, and fostered professional growth despite time constraints and logistical challenges. The short implementation period prompted participants to adapt quickly, contributing to increased agility and innovation in lesson design.